Government policies and data protection in Ecuador: ideas around health emergency - Ordóñez Pineda, Luis (2022)
This research aims to demonstrate the need to enhance the fundamental right to data protection through public policy formulation and implementation in Ecuador. For this purpose, this study examined the public policy “For a safe internet for children and adolescents” as well as three rulings of the Constitutional Court. To this end, it is relevant to support instances that guarantee data protection and to underline that handling sensitive data can affect the exercise of the rights of persons affected by the health emergency. In the face of illegitimate intrusions into the privacy of individuals, public policies help to strengthen and generate prevention and awareness programs regarding the protection of personal data, both regionally and in Ecuador.